Application of a SWOT-FANP method - Lee, Yun-Huei (Technological and Economic Development of Economy, 2013)
Strengths, weaknesses, opportunities, and threats (SWOT) analysis is an effective strategic planning tool for the development of strategy formulation, but its main weakness is being incapable of quantitatively determining the weights and effects of alternative strategic criteria. Some studies’ use of SWOT with analytic hierarchy process (AHP) would enable decision-makers to obtain-through pairwise comparisons-a relative priority of each criterion, so that the results from quantitative measures could overcome SWOT's central shortcoming. However, these studies neglect critical relationships or dependencies among SWOT factors. In this study, I propose a quantitative SWOT that rests on fuzzy analytic network process (FANP) methodology, includes possible dependencies among SWOT factors and permits the elimination of decision-makers’ uncertain and vague preferences. To this end, I chose the Taiwan biotech pharmaceutical industry as an illustrative example. This study demonstrates and validates that such an enhanced methodology is viable and highly capable of providing enriched insights regarding strategic decision-making management in complex real-world situations.